Early Gallbladder Carcinoma: Demographic Features, Associated Factors and Surgical Outcomes in Tertiary Care Hospitals of Bangladesh (Bangladesh Medical Journal, 2025)
Gall bladder carcinoma is the most prevalent biliary tract malignancy worldwide. It has no specific symptoms. Symptoms begin with the advancement of disease, and it terminates the life rapidly. Therefore, early diagnosis and intervention lead to positive results, and better outcomes could be assured following surgery. This cross sectional descriptive study was conducted among admitted patients, in the Department of Hepato-Biliary-Pancreatic Surgery and Liver Transplant (HBPS & LT) of BIRDEM General Hospital, Ibn Sina Specialized hospital and Crescent Gastro Liver and General Hospital in Dhaka City from January 2022 to June 2024, over a period of 2 years and 6 months. Most of the data (90%) were obtained from BIRDEM and rest 10% from above mentioned hospitals. The initial estimated sample size was 86; however, after applying the inclusion and exclusion criteria, only 40 cases were included due to data limitations. The study included all histopathologically verified early gallbladder carcinoma cases, but excluded those with signs of advanced malignancy. Cases were selected irrespective of age or sex, anatomical distribution, clinical features, risk factors, histological type, and surgical outcomes. After receiving ethical approval from the Ethical Committee and verbal consent from the patients, data were collected through face-to-face interviews and observations using a pre-testing questionnaire check list specifically designed for the study by the researcher. A total 40 cases were included in the study. The peak incidence of gallbladder carcinoma was observed in 5th and 6th decades of life with the mean age of the cases being 58.12±7.75 years and their age range was 35 to 80 years. Female was predominance; where, male female ratio was 1:2.34. Gall stone (80%) was the most common associated factor and mostly diagnosed incidentally (92.5%). Mostly done procedure was laparoscopic cholecystectomy and it was about 90% .Tumor involve fundus of the gallbladder in 55% cases and most of these were adenocarcinoma (90%). After surgery, wound infection rate was 7.5% and port site hernia was 5%, however there was no recurrence and survivability was 97.5% within the duration of study periods. Early surgical intervention brings good result in the management of early gallbladder carcinoma.Bangladesh Med J. 2024 Jan; 53(1): 33-38